The impact of early life gut colonization on metabolic and obesogenic outcomes: what have animal models shown us?. (24th September 2015) - Wallace, J. G.; Gohir, W.; Sloboda, D. M.
Abstract : The rise in the occurrence of obesity to epidemic proportions has made it a global concern. Great difficulty has been experienced in efforts to control this growing problem with lifestyle interventions. Thus, attention has been directed to understanding the events of one of the most critical periods of development, perinatal life. Early life adversity driven by maternal obesity has been associated with an increased risk of metabolic disease and obesity in the offspring later in life. Although a mechanistic link explaining the relationship between maternal and offspring obesity is still under investigation, the gut microbiota has come forth as a new factor that may play a role modulating metabolic function of both the mother and the offspring. Emerging evidence suggests that the gut microbiota plays a much larger role in mediating the risk of developing non-communicable disease, including obesity and metabolic dysfunction in adulthood. With the observation that the early life colonization of the neonatal and postnatal gut is mediated by the perinatal environment, the number of studies investigating early life gut microbial establishment continues to grow. This paper will review early life gut colonization in experimental animal models, concentrating on the role of the early life environment in offspring gut colonization and the ability of the gut microbiota to dictate risk of disease later in life.